2015
DOI: 10.1159/000368292
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Functions of Hereditary Hearing Loss Patients with <b><i>GJB2</i></b> Mutations

Abstract: Objectives: Mutations in the GJB2 gene have been of particular interest as it is the most common causative gene for congenital deafness in all populations. Detailed audiological features, including genotype-phenotype correlations, have been well documented. However, in spite of abundant gene as well as protein expression in the vestibular end organs, neither vestibular symptoms nor vestibular functions have yet been elucidated. In the present study, vestibular functions were evaluated in patients diagnosed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
2
6
1
Order By: Relevance
“…Dominant GJB2 mutations related to syndromic hearing loss and skin manifestations were excluded in Family 304. Compared with the results of previous studies in which subjects with bilateral GJB2 mutations showed normal caloric responses and significantly lower cVEMP amplitudes, the vestibular function assessed by caloric tests and cVEMP were normal in this study 7 . Notably, hearing loss is an etiologically heterogeneous trait that is related to many genetic and environmental causes 8 .…”
Section: Discussioncontrasting
confidence: 91%
“…Dominant GJB2 mutations related to syndromic hearing loss and skin manifestations were excluded in Family 304. Compared with the results of previous studies in which subjects with bilateral GJB2 mutations showed normal caloric responses and significantly lower cVEMP amplitudes, the vestibular function assessed by caloric tests and cVEMP were normal in this study 7 . Notably, hearing loss is an etiologically heterogeneous trait that is related to many genetic and environmental causes 8 .…”
Section: Discussioncontrasting
confidence: 91%
“…In another study on seven subjects with DFNB1 HI, vestibular dysfunction was bilateral in one subject and unilateral in four subjects, as revealed by either VEMP recording or the caloric test (Kasai et al, 2010 ). In a series of 23 subjects with two mutant DFNB1 alleles, only 2 had unilaterally abnormal caloric responses, but 17 showed decreased VEMP amplitudes (Tsukada et al, 2015 ), which again would suggest a saccular dysfunction. No patient in this series complained of vertigo or dizziness (Tsukada et al, 2015 ).…”
Section: Clinical Features Of Dfnb1 Himentioning
confidence: 98%
“…In a series of 23 subjects with two mutant DFNB1 alleles, only 2 had unilaterally abnormal caloric responses, but 17 showed decreased VEMP amplitudes (Tsukada et al, 2015 ), which again would suggest a saccular dysfunction. No patient in this series complained of vertigo or dizziness (Tsukada et al, 2015 ). In another study, a survey was used to assess symptoms of vestibular dysfunction in subjects with two GJB2 mutant alleles, and 127 out of 235 participants (54%) reported dizziness and vertigo (Dodson et al, 2011 ).…”
Section: Clinical Features Of Dfnb1 Himentioning
confidence: 98%
“…Concerning vestibular function, the patients showed normal vestibular function, as evaluated by caloric test and cVEMP ( Figure 5), and none of the patients showed vestibular symptoms. 33 Vestibular compensation may be related to these complications, and this possibility should be further examined in future studies. Weegerink et al 8 reported that 5 out of 9 patients showed mild hyperreflexia/hyporeflexia on rotatory and caloric tests.…”
Section: Discussionmentioning
confidence: 96%
“…32 A similar discrepancy between gene expression, vestibular testing, and vestibular symptoms has also been reported for GJB2 -associated deafness. 33 Vestibular compensation may be related to these complications, and this possibility should be further examined in future studies.…”
Section: Discussionmentioning
confidence: 96%